Analisis Tindak Tutur Representatif dan Impositif dr. Tirta pada Video Kesehatan #suaratirta dalam Kanal YouTube Tirta PengPengPeng - Allamanda Kusumaning Anjora; Erika Anggraeni; Hesti Kurnianingtyas; Meisa Nuri Aisyah; Nafhisa Diva Salsabella; Asep Purwo Yudi Utomo; Antonius Edi Nugroho; Winda Dwi Hudhana (Pusat Riset dan Inovasi Nasional, 2025)
Pragmatics is one of the branches of semiotics, alongside semantics and syntax, that examines the relationship between signs and their usage. Speech acts, or activities involving a speaker and a listener, are divided into five types: representative, commissive, directive, expressive, and declarative speech acts. This study primarily focuses on one of these types—representative speech acts. The researcher collected health-related videos tagged #suaratirta from the YouTube channel Tirta PengPengPeng using the Listen, Free, Engage, Speak (SBLC) method along with note-taking techniques. The data were then analyzed using matching and distributional techniques. The findings reveal 93 instances of representative speech acts, detailed as follows: a) 13 declarative statements, b) 27 explanatory statements, c) 42 informative statements, d) 9 warning statements, and e) 2 speculative statements. Additionally, 19 instances of impositive speech acts were identified, categorized as follows: a) 5 directive statements, b) 7 advisory statements, c) 2 prohibitive statements, and d) 5 interrogative statements.